Mind Mapping Dalam Pembelajaran Struktur Atom Pada Siswa Kelas X SMA Negeri 1 Palu - Muhamad, Sirhan; Solfarina, Solfarina; Ratman, Ratman (Universitas Tadulako, 2015)
Teaching and learning is a process involving interaction with active communication between students and teacher in educational activities. Therefore we need a method of learning that is focused to the students. That is why required a learning model that empowers students to be more actively involved in the learning process at schoolis mind mapping. The aim of this study is to describe and determine the differences in use mind mapping in class X SMA Negeri 1 Palu on the subject of atomic structure. The population in this research was class X (n =408 student) academic year 2013/2014. The sample of this research was class X 3 (using mind mapping method) while class X 5 as the control class (using concept maps), both of class have 34 students. Data collected was conducted by instruments, namely test results of studying chemistry at the atomic structure which has been validated before. The examination of data was conducted by using statistical analysis two tailed t-test with the prerequisite tests (normality and homogeneity test). The average score in the experimental class is 77.15 while the average score in control class is 68.44. Based on statistical hypothesis testing to two tailed t-test obtain tcalculation = 10.89 > ttable = 2.00 at α = 0.05 with criteria if Ho is accepted tcalculationttable(1–α), (n1 + n2). As result, H0 is not accepted due to tcalculation was in the rejection area of Ho. This indicates that there are differences in student learning outcomes through the application between the mind mapping and the concept maps methods in class X SMA Negeri 1 Palu.